Change in Retirement Plans Among Midlife Couples During an Economic Recession. (4th June 2019) - Yorgason, Jeremy B; Segel-Karpas, Dikla; Wheeler, Brandan E; Malig Canlas, Jerevie; Smith, Jamie
Abstract: Objective: Although research has investigated financial planning for retirement, less is known about how adults plan their retirement activities. Even less is known about couples' congruence and incongruence in retirement activities planning. The authors examined husband and wife reports of retirement plans across a 5-year period that involved a U.S. economic recession. Method: Using data from 335 midlife couples who participated in the Flourishing Families project, retirement plans were grouped into five categories—family, leisure, volunteer, work, and uncertain. We estimated probit dyadic structural equation models to explore longitudinal predictors of retirement plans. Results: Results indicated mean differences in retirement plans between husbands and wives, and also across time that might have been influenced by surrounding economics. Wife poor health, number of children, both spouses working, and financial assets were linked with the likelihood of reporting certainty in retirement plans. Greater retirement uncertainty was predicted by lower marital quality, higher financial adjustments, lower education, and ethnic diversity. Conclusion: Husband and wife reports of retirement plans are not always congruent, and plans in retirement can be affected by large scale changes in the U.S. economy.